Melatonin and sleep responses to normobaric hypoxia and aerobic physical exercise: A randomized controlled trial - de Aquino Lemos, Valdir; dos Santos, Ronaldo Vagner Thomatieli; Antunes, Hanna Karen Moreira; Behn, Claus; Viscor, Gines; Lira, Fabio Santos [UNESP]; Bittar, Irene Guarido Luz; Caris, Aline Venticinque; Tufik, Sergio; De Mello, Marco Tulio (Elsevier, 2018)
This work evaluated the effects of moderate physical exercise performed under hypoxic conditions on melatonin and sleep. Forty healthy men were randomized into four groups: Normoxia (N) (n = 10); Hypoxia (H) (n = 10); Exercise under Normoxia (EN) (n = 10); and Exercise under Hypoxia (EH) (n = 10). The observation period for all groups was approximately 36 h, beginning with a first night devoid of any intervention. Aerobic exercise was performed by the EN and EH groups on a treadmill at 50% of the ventilatory threshold intensity for 60 min. Sleep evaluation was performed on the 1st and 2nd nights. Venous blood samples for the melatonin measurement were obtained on the 1st and 2nd days at 7:30 AM as well as on the 1st and 2nd nights at 10:30 PM. On the 2nd night, melatonin was higher in the H group than in the N group, but both were lower than values of the EH group. The nocturnal increase in melatonin was inversely correlated with the oxygen saturation of hemoglobin (SaO2%) on the 2nd night in the H group and on the 2nd day in the EH group. Diurnal remission of nocturnal melatonin appeared to be postponed in the H group and even more so in the EH group. Thus, normobaric hypoxia, which is equivalent to oxygen availability at an altitude of 4500 m, acutely increases melatonin. Moreover, diurnal remission of the nocturnal increase in melatonin seems to be delayed by hypoxia alone but even more so when acting together with exercise.
Keywords: Exercise; Hypoxia; Melatonin